Anteseden Struktur Modal: Studi Kasus Perusahaan Sektor Kesehatan Yang Listing Di Bursa Efek Indonesia Periode 2018-2022 - Patricia Steffina Mawitjere; Chairul Adhim; Gaby Dainty Julliet Roring; Ferly Christian Kolinug (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Finding empirical evidence regarding the antecedents of the capital structure of Healthcare Sectors listed on the Indonesian Stock Exchange between 2018 and 2022 is the aim of this study. Profitability, asset structure, firm size, and liquidity are the study’s independent variables. while The capital structure proxied by Debt to Equity Ratio is the dependent variable. This study used panel data from 15 companies selected through purposive sampling method. Fixed Effect Model is the model employed in this study. The study’s finding indicate that while profitability and liquidity have no impact on capital structure, asset structure and firm size have a positive and significant impact.